The Jãba: Dugout Canoes of the Emberá – An Ethnoarchaeological Analysis in Darién and the Emberá–Wounaan Territory in Panama - Alberda, Abner (The international journal of nautical archaeology, 2024)
This article presents the findings from the field season of 2021–2022 conducted by the Proyecto Etnoarqueológico Jãba in the province of Darién and the Emberá Wounaan Territory, which are the primary territories of the Emberá people in Panama. With an ethnoarchaeological approach, the study documents the exploitation of timber forest resources, the construction of traditional watercrafts, their main uses, and the changes they have undergone. The research is grounded in participant observation and semi-structured interviews, focusing specifically on the construction process of dugout canoes (jãba), including ‘piraguas’, ‘esteleadoras’, as well as boats and rafts.